Studies on variability of some morphological characters in fennel (Foeniculum vulgare Mill.) 1 - I D Patel, D G Patel, P S Patel (Journal of Spices and Aromatic Crops, 2008)
Analysis of variability carried out for 15 characters in 36 diverse genotypes of fennel (Foeniculumvulgare) at Jagudan (Gujarat) revealed highly significant differences among genotypes for allthe characters studied. High genotypic and phenotypic variances were observed for days to50% flowering, days to 50% maturity, plant height, plant height up to main umbel, totalbranches plant-1, number of seeds main umbel-1 and seed yield plant-1. The highest genotypiccoefficient of variation was observed for volatile oil content in seed followed by total branchesplant-1 and number of seeds main umbel-1. Heritability estimates were high for seed yieldplant-1, days to 50% flowering, number of primary branches plant-1, total branches plant-1,test weight and volatile oil content. High genetic advance as percentage of mean was recordedfor seed yield plant-1, days to 50% flowering, primary branches plant-1, total branchesplant-1, effective umbels plant-1, number of umbellates umbel-1, number of seeds mainumbel-1, test weight and volatile oil content, suggesting that phenotypic selection for thesetraits would be effective. Overall, it is suggested that for improving yield in fennel, moreemphasis should be given to plant height, primary branches plant-1, total branches plant-1and effective umbels plant-1.